Optimal $L^2$ Extensions of Openness Type and Related Topics - Xu, Wang; Zhou, Xiangyu (Comptes Rendus. Mathématique)
We establish several optimal $L^2$ extension theorems of openness type on weakly pseudoconvex Kähler manifolds. We prove a product property for certain minimal $L^2$ extensions, which generalizes the product property of Bergman kernels. We describe a different approach to the Suita conjecture and its generalizations, which is based on a log-concavity for certain minimal $L^2$ integrals.